Caracterização estrutural da embriologia em Tillandsia aeranthos (Lois.) L. B. SM. (Tillandsioideae-bromeliaceae) - Spat, Cristiele (2012)
Bromeliaceae owns a huge diversity of species in the Neotropical region, comprising about 3140 species, in which 551 consist of the genus Tillandsia. The article aims the descritption, of the anther development and ovule as the esporogenesis and gametogenesis characterization as well, in order to make easier both the taxonomy and philogeny of the family, which is still in process of change. Tillandsia aeranthos (Lois.) L. B. Sm. contains six stamens flowers; superior, tricarpellate and trilocular ovary. The pattern of development of the anther wall is characterized as mixed-type. Androsporangium is formed by epidermis, middle layers, endothecium and tapetum. The tapetum is the secretor-type. Meiosis is the successive-type with cleavage of the centrifugal type. The tetrads formed are decussate or isobilateral. The first division of the pollen is preceded by vacuolation, it is assymmetric and produce both generative and vegetative cells. The two cells formed are separated by a callose wall. The mature grain pollen is bicelullar. The ovule of Tillandsia aeranthos is anatropus, bitegmic and crassinucellate, with axial placentation. The ovule originates in the subdermal layer (zone II) of the placentae. The integument nucellar epidermis is originated by divisions in the dermal layers. One to three ginospore mother celss, which are originated by divisions in archesporial cell, undergo meiotic divisions development a linear tetrad, with presence callosic wall. Only the chalazal ginospore becomes functional. The functional ginospore differs in that a gametophyte uninucleate after mitosis and yields a two-nucleate and four-nucleate gametophyte. The female gametophyte has a monosporic origin and a Polygonum-type development. The female gametophyte consists of two synergids, an egg cell, three antipodes and two polar nuclei. Polar nuclei fuse prior to fertilization.